Electronic digital laboratory for teaching natural science, engineering and biomedical disciplines in educational institutions - Yakimenko, Yurіy; Orlov, Anatolіy; Zhuikov, Valeriy; Spіvak, Vіktor; Bogdan, Oleksandr (Видавництво Львівської політехніки, 2012)
The article represents information about development of an electronic digital laboratory for teaching and learning science and natural sciences, engineering and biomedical sciences.
Keywords: Electronic digital educational laboratory; natural science; engineering and biomedical disciplines